2011
DOI: 10.1586/ern.11.82
|View full text |Cite
|
Sign up to set email alerts
|

Unmet treatment needs in schizophrenia patients: is asenapine a potential therapeutic option?

Abstract: Adverse metabolic events, such as increased adiposity, hyperglycemia, diabetes mellitus and dyslipidemia, have been associated with treatment using atypical antipsychotic medications. However, the complexity of some of the reports on this problem and marketing efforts in this area may make it difficult for psychiatrists to remain fully and accurately informed about the metabolic complications of atypical antipsychotic therapy. Little is currently known about how psychiatrists view what they have read or heard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 157 publications
(177 reference statements)
1
7
0
Order By: Relevance
“…However, the mortality rate from cardiovascular disease in schizophrenia patients is reportedly 2.5-fold higher than that in the general population, 23 implying that treatment-induced metabolic abnormalities may induce cardiovascular diseases. 4 In the present study, Kaplan-Meier analysis showed that the sustained efficacy rate in subjects who responded to treatment in the preceding short-term study (PANSS responders) reached approximately 50% at 6 months and did not change significantly thereafter until 12 months, regardless of whether they were in the placebo or asenapine group in the feeder study. The results of the feeder study showed that asenapine treatment resulted in a significant improvement in the PANSS total score compared with placebo.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, the mortality rate from cardiovascular disease in schizophrenia patients is reportedly 2.5-fold higher than that in the general population, 23 implying that treatment-induced metabolic abnormalities may induce cardiovascular diseases. 4 In the present study, Kaplan-Meier analysis showed that the sustained efficacy rate in subjects who responded to treatment in the preceding short-term study (PANSS responders) reached approximately 50% at 6 months and did not change significantly thereafter until 12 months, regardless of whether they were in the placebo or asenapine group in the feeder study. The results of the feeder study showed that asenapine treatment resulted in a significant improvement in the PANSS total score compared with placebo.…”
Section: Discussionsupporting
confidence: 47%
“…Compared with first‐generation antipsychotics, second‐generation antipsychotics are generally associated with fewer extrapyramidal adverse events and block receptors other than dopamine receptors, such as serotonin receptors, suggesting that they are effective in improving negative symptoms and cognitive impairment in addition to positive symptoms. Thus, these medications may have a favorable impact on improving patient quality of life (QOL) and social reintegration 2,4 . However, second‐generation antipsychotics have been associated with side effects such as weight gain and hyperprolactinemia 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…Historically, pharmacological treatments have focused on dopamine D 2 receptor blockade to control the positive symptoms of schizophrenia, while negative and cognitive symptoms often persist (Abi-Dargham 2014 ; van Os and Kapur 2009 ). Second generation anti-psychotics, which also inhibit a range of other receptors, have been developed, but they vary in their effectiveness across mood domains (Lublin et al 2005 ; Pompili et al 2011 ). In addition, second generation anti-psychotics have differing levels of risk for weight gain and hyperprolactinemia (De Hert et al 2012 ; Kane 2011 ; Tandon et al 2010 ), which can negatively affect treatment adherence (Kane 2011 ; Lieberman et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…People with schizophrenia are thought to be less likely to seek and use medical care, they engage in risk-taking behaviour often fail to comply with their treatment regimes (Saha et al, 2007). It is now recognized worldwide that identifying and dealing with physical illness would benefit individual patients, improving their quality of life, extending their life expectancy, and leading to improvements in their economic and social welfare (Pompili et al, 2011).…”
Section: Introductionmentioning
confidence: 99%